Farm-level actions towards water pollution control: the role of nutrient guidance systems - Wilson, Paul (Wiley, 2015)
Enhanced agricultural pollution control will be required to ensure compliance with the 2015 European Union (EU) Water Framework Directive. Drawing upon data from an on-farm survey with 1370 farmers and growers across England, combined with production, financial, farm and farmer characteristic data from the English Farm Business Survey, this paper investigates farmer attitudes and actions towards water pollution control. Significant differences in practices taken to reduce or prevent pollution were observed by farm type, EU region, farmer education level and use or absence of a nutrient guidance system. However, no significant differences were observed in financial output–input performance of arable farmers by use and non-use of a nutrient guidance system. Nutrient guidance systems were, however, associated with a greater uptake of practices to reduce or prevent water pollution. Water companies could build upon upstream land management approaches to provide targeted investment in extension services to incentivise on-farm use of these guidance systems.